2015
DOI: 10.1590/1982-0194201500068
|View full text |Cite
|
Sign up to set email alerts
|

Tendência de hospitalizações por diabetes mellitus: implicações para o cuidado em saúde

Abstract: Objective: To analyze the trend in hospitalizations for diabetes mellitus in a period of 15 years, according to gender and age group. Methods: Descriptive study, with time series data from hospitalization for diabetes mellitus in individuals of both genders, aged 20 or more, data obtained in the information system of the unified health system and analyzed according to descriptive statistics and polynomial regression. Results: A total of 117,717 hospitalizations were registered, 61.6% were women. The general tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
0
8
0
9
Order By: Relevance
“…This fact directly affects the quality of life and generates high costs to health services. 13 It is known that diabetic complications are composed of macrovascular (coronary artery disease, cerebrovascular disease and peripheral vascular disease) and microvascular (retinopathy, nephropathy and neuropathy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact directly affects the quality of life and generates high costs to health services. 13 It is known that diabetic complications are composed of macrovascular (coronary artery disease, cerebrovascular disease and peripheral vascular disease) and microvascular (retinopathy, nephropathy and neuropathy).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary that health professionals develop promotion and health prevention actions, offering people living with diabetes, information about the disease, warning about the complications of diabetes, and also selfcare actions related primarily to the adoption of healthier lifestyles in order to provide a more appropriated self-care. 1,13 Educational practices in health in this context recognize the importance of new strategies that prioritize the autonomy of individuals with DM and conscious decision-making managers of their own health 3 , in which the attention to DM should return for the provision of clinical and educational interventions informed by scientific evidence. 17 Health education, offered by primary care services is one strategy that helps to decrease the high prevalence of complications in people with diabetes that get worse due to the lack of self-care realization, especially in aspects related to proper nutrition, physical exercise and proper use of antidiabetic medication, when prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…We should emphasize that hospitalizations commonly reflect an inadequate DM control. In this sense, a study carried out in the state of Paraná showed an increasing tendency of hospitalization due to DM in men aged 50–59 years and in those older than 80 years [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, acredita-se que haja o predomínio das mulheres na utilização de serviços de saúde, o que corrobora o resultado de um ensaio clínico randomizado realizado, cujas mulheres apresentaram 1.4 vezes mais chance de utilizarem o serviço de saúde quando comparadas com os homens 20 .…”
Section: Saúde E Pesquiunclassified